How to Make Students Ūlū al-Albāb: A Case Study at UIN Sunan Gunung Djati Bandung During the Covid-19 Pandemic - Sadiah, Dewi (Didaktika Religia, 2022)
It is the responsibility of lecturers to instill knowledge and good morals in their students, whether in the lecture hall or in online classes, as was the case during the 2020 pandemic caused by the novel coronavirus. This article aims to describe lecturers’ efforts to turn their students into “people with intellect” (ūlū al-albāb) who are critical, reflective and morally mature individuals. This study is based on qualitative research, employing data mining through observation, learning documentation, and interviews. The data were collated and subjected to analysis in order to reduce, present, conclude and verify them. The research was conducted at UIN Sunan Gunung Djati Bandung, with a particular focus on the manifestation of ūlū al-albāb traits among the student population. The findings revealed that the lecturers employed a distinctive approach in the online setting, encompassing a gentle approach (maw’ziah hasanah), attention, affection, exercises, assignments, discussions, and the provision of solutions. While conducting their lessons online, the lecturers continued to support and evaluate their students’ attitudes and academic progress, without noticing any decline in their mid-semester and final examination results. There was also a notable improvement in the students’ critical thinking abilities, as evidenced by the quality of their thesis proposals. The students demonstrated consistent mastery of the learning material and a creative approach to research.